Pretreatment biopsy analysis of DAB2IP identifies subpopulation of high‐risk prostate cancer patients with worse survival following radiation therapy. (16th October 2015) - Jacobs, Corbin; Tumati, Vasu; Kapur, Payal; Yan, Jingsheng; Xie, Xian‐Jin; Hannan, Raquibul; Hsieh, Jer‐Tsong; Kim, Dong Wook Nathan; Saha, Debabrata
Abstract : About one‐fourth of men with high‐risk prostate cancer may have reduced tumor suppressor DAB2IP expression which makes their tumors more radio‐resistant and aggressive, and it ultimately leads to higher malignancy‐specific mortality following definitive radiotherapy and androgen deprivation. This is the first study showing a survival detriment in prostate cancer linked to DAB2IP status. Abstract: Decreased expression of tumor suppressor DAB2IP is linked to aggressive cancer and radiation resistance in several malignancies, but clinical survival data is largely unknown. We hypothesized that pretreatment DAB2IP reduction would predict worse prostate cancer‐specific survival (PCSS). Immunohistochemistry of pretreatment biopsies was scored by an expert genitourinary pathologist. Other endpoints analyzed include freedom from biochemical failure (FFBF), castration resistance‐free survival (CRFS), and distant metastasis‐free survival (DMFS). Seventy‐nine patients with NCCN‐defined high‐risk prostate cancer treated with radiotherapy from 2005 to 2012 at our institution were evaluated. Twenty‐eight percent (22/79) of pretreatment biopsies revealed DAB2IP‐reduction. The median follow up times were 4.8 years and 5.3 years for patients in the DAB2IP‐reduced group and DAB2IP‐retained group, respectively. Patients with reduced DAB2IP demonstrated worse outcome compared to patients retaining DAB2IP, including FFBF (4‐year: 34 vs. 92%; P  < 0.0001), CRFS (4‐year: 58 vs. 96%; P  = 0.0039), DMFS (4‐year: 58 vs. 100%; P  = 0.0006), and PCSS (5‐year: 83 vs. 100%; P  = 0.0102). Univariate analysis showed T stage, N stage, and Gleason score were statistically significant variables. Pretreatment tumor DAB2IP status remained significant in multivariable analyses. This study suggests that about one‐fourth of men with high‐risk prostate cancer have decreased tumor expression of DAB2IP. This subpopulation with reduced DAB2IP has a suboptimal response and worse malignancy‐specific survival following radiation therapy and androgen deprivation. DAB2IP loss may be a genetic explanation for the observed differences in aggressive tumor characteristics and radiation resistance. Further study into improving treatment response and survival in this subpopulation is warranted.